Redescription of the genus Turnicola Clay & Meinertzhagen, 1938 (Phthiraptera: Ischnocera) and its type species - Chen, Daojian; Grossi, Alexandra A.; Zhang, Min; Chen, Xiaowen; Zou, Fasheng; Gustafsson, Daniel R. (Zootaxa, 2026)
The genus Turnicola Clay & Meinertzhagen, 1938a is redescribed and illustrated in detail for the first time, together with specimens here regarded as the type species of this genus, Lipeurus angustissimus Giebel, 1866. As the type series of this species has been lost, we here designate a neotype for L. angustissimus from specimens collected from the type host in Guangdong, China. Specimens from two different host species have the same COI genotype, indicating that Turnicola angustissimus is more widely distributed than previously thought. Differences in the louse prevalences between the two host species suggest that some, yet unknown, ecological factors may impact their louse communities.